Controversial Issues: Pro Mechanical Cardiopulmonary Resuscitation - Dyson, Kate; Stub, D.; Bernard, S.; Smith, K. (2018)
High-quality cardiopulmonary resuscitation, in particular chest compressions, is a key aspect of out-of-hospital cardiac arrest (OHCA) resuscitation. Manual chest compressions remain the standard of care; however, the extrication and transport of patients with OHCA undermine the quality of manual chest compressions and risk the safety of paramedics. Therefore, in circumstances whereby high-quality manual chest compressions are difficult or unsafe, paramedics should consider using a mechanical device. By combining high-quality manual chest compressions and judicious application of mechanical chest compressions, emergency medical service agencies can optimize paramedic safety and patient outcomes.